Effect of Capital Structure, Company Size and Profitability on the Stock Price of Food and Beverage Companies Listed on the Indonesia Stock Exchange - Murniati, Sitti (Information Management and Business Review, 2016)
The purpose of this study was to analyze the effect of capital structure proxy for debt to asset ratio (DAR) and the debt to equity ratio (DER), company size and profitability are proxied by return on assets (ROA), return on equity (ROE) and net profit margin (NPM) to the stock price on the company’s Food and Beverage listed on the Indonesia Stock Exchange. This study uses Associative approach. The population in this study is the Food and Beverage companies listed in Indonesia Stock Exchange year period 2011 to 2014. Sampling method used is purposive sampling and the amount of samples obtained is 11 companies with 44 observations. Hypotheses were tested using multiple regression analysis. Results of the study were 1) capital structure proxy for debt to asset ratio (DAR) significant negative effect on stock prices, this means that if a decline in the value of DAR, the stock price will rise, 2) capital structure proxy for debt to equity ratio (DER) significant positive effect on stock prices, it means that the higher the value of DER then be followed by a decrease in stock prices, 3) The company size significant positive effect on stock prices, this suggests that the relationship between the SIZE with stock prices in the same direction, if SIZE increases, the stock price will increase, 4) profitability is proxied by return on assets (ROA) significant positive effect on stock prices, this means that the assets of the company to make a profit can affect stock prices, 5) profitability proxied with a return on equity (ROE) significant negative effect, this means that if a decline in ROE it will be followed by a decrease in stock prices, and 6) Profitability which is proxied by net profit margin (NPM) significant negative effect on stock prices, this means that while the net profit increased, the total sales will rise this is due to the high costs incurred by the company so that NPM has no effect on stock prices.